Bilingual Educational Dictionary on the Special Subject for Foreign Students. - Груцяк, В. И. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article describes the principle of the creation of bilingual educational glossary for foreign students who study special subjects in a foreign language. The main target of these dictionaries is to provide definitions of terms and their standard combinations with other nouns, adverbs, participles, verbs. These terms are introduced foreign students to the essential system concepts of the discipline explaining the nature, similarities and differences between concepts that are interpreted, provide information about the phonetic, grammatical and word-formation properties of lexical units that denote these concepts